2018
DOI: 10.1002/ppap.201700234
|View full text |Cite
|
Sign up to set email alerts
|

A review on the recent progress, challenges, and perspectives of atmospheric‐pressure cold plasma for preparation of supported metal catalysts

Abstract: Supported metal catalysts are of great importance in energy and environmental applications. Atmospheric-pressure (AP) cold plasma, generally generated by dielectric barrier discharge and cold plasma jet, has been proved to be a fast, facile, and energy efficient method for fabricating supported metal catalysts. In this review, the recent progress, challenges, and perspectives of AP cold plasma for synthesizing supported metal catalysts are discussed. Focus is placed on recent work demonstrating the discharge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 160 publications
0
80
0
Order By: Relevance
“…The work of Di et al has demonstrated the reduction of some metal ions (Au, Pd, Ag and Pt) using alcohol 11 and CO 12 cold plasmas, in the absence of hydrogen. 13 However, plasmas are an accessible source of free electrons, and as a consequence, they have been implicated to be effective at driving chemical change at liquid, soft solid and solid surfaces. 5b, 14 Richmonds, Brettholle and Meiss demonstrated charge-transfer processes at the plasma/liquid interface by positioning a plasma discharge in contact with a liquid electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Di et al has demonstrated the reduction of some metal ions (Au, Pd, Ag and Pt) using alcohol 11 and CO 12 cold plasmas, in the absence of hydrogen. 13 However, plasmas are an accessible source of free electrons, and as a consequence, they have been implicated to be effective at driving chemical change at liquid, soft solid and solid surfaces. 5b, 14 Richmonds, Brettholle and Meiss demonstrated charge-transfer processes at the plasma/liquid interface by positioning a plasma discharge in contact with a liquid electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the conventional thermal process, the catalyst preparation with plasma is not based on the thermal effect, but on the inelastic collision of those energetic species (free electrons, radicals, excited species and ions) with catalyst precursors to accomplish the purpose of calcination or treatment. Catalyst preparation with plasma has attracted increasing interest since the 1990s [25][26][27][28][29][30][31][32][33][34], and a variety of plasmas, such as glow discharge, radio frequency discharge, microwave discharge, and dielectric barrier discharge, were employed for calcination and reduction of supported catalyst, which can make metal highly dispersed on a support with a narrow distribution of particle size, manipulate metal-support interaction, and shorten the time of catalyst preparation due to high reaction rates in the plasma process. Besides, with regard to the characteristic of low temperature, plasma removal of template was well developed for synthesis of microporous and mesoporous materials, instead of thermal removal that could destroy the porous structure of the materials [35].…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of the APPJ is due to the fact that it does not require a vacuum chamber, the shapes and sizes can be easily modified to suit the objectives, and it is inexpensive. There are several ways to generate APPJ such as direct current discharge, microwave discharge, and dielectric barrier discharge (DBD) . These discharge methods have their own unique features.…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to generate APPJ such as direct current discharge, microwave discharge, and dielectric barrier discharge (DBD). [5][6][7] These discharge methods have their own unique features. The DBD devices have the simplest configurations because they are composed of only one or two dielectric layers between two metal electrodes, and there is an increasing interest in the DBD plasma jets and their applications.…”
mentioning
confidence: 99%